Okara biochar immobilized calcium-alginate beads as eosin yellow dye adsorbent - Adhitasari Suratman; Desi Nur Astuti; Pinastya Purwakaning Kusumastuti; Sri Sudiono (Results in Chemistry, 2024)
Okara biochar was obtained through the pyrolysis process and continued by encapsulation into beads form to ensure biochar does not leach into the environment. The utilization of okara biochar beads (OBB) as an adsorbent of eosin yellow (EY) dye was developed due to its porosity and high surface area properties. The adsorption kinetics of EY by OBB follows the pseudo second order (PSO) model while the adsorption isotherms follow the Freundlich isotherm model with reaction rate constants of 19.71 g mg−1 min−1 and KF = 12.12 L mol−1. The results show that OBB is easily separated from water and has an adsorption percentage up to 80%.